Kajian Efektivitas Penggantian Alat Tangkap Cantrang Menjadi Gillnet Millenium di Banyutowo, Pati, Jawa Tengah - Neneng Evy Yulieny; Achmad; Nimmi (Graduate School Bogor Agricultural University (SPs IPB), 2020)
This study’s background was based on the prohibition of cantrang’s operation. To reduce impact of this ban, the Government was replacing cantrangs with another fishing gears which are considered more environmentally friendly. In Banyutowo, Pati Residence, “cantrang” was replaced with Gillnet Millennium. This study aims to determine the pattern of fishing season of some of the dominant fish species caught around Banyutowo and to analyze the effectiveness of replacing fishing gear, from cantrangs into gillnet millenium at Banyutowo. The fishing season indeks was analyzed using the moving average method. The types of fish analyzed in this study were the dominant fish caught in the Banyutowo waters with cantrang and gillnet such as Kuniran, Squid, Pari, Manyung, Beloso, Kuro and Tigawaja fish. Analysis of the effectiveness of replacing cantrang with the gillnet millenium in Banyutowo was carried out at the process, and output stages. The results showed that some of the most landed fish in PPI Banyutowo had different fishing seasons. The peak season for fishing in Banyutowo occurs in December (West season) and lowest in July (East season). The evaluation of the effectiveness of replacing cantrang into the gillnet millennium in Banyutowo at the process stage shows ineffective results, and at the output stage shows very ineffective results.